A meta-analysis to examine dental and skeletal effects of the twin block appliance compared to that of the forsus appliance in the class ii correction among teenagers - Tafa, Anjeza (İstanbul Medipol Üniversitesi, Sağlık Bilimleri Enstitüsü, 2022)
The aims of this meta-analysis were to screen chosen publications on twin block and Forsus fatigue resistant device, in order to generalize their skeletal and dentoalveolar effects and to make a comparison of conjunction results of each treatment approach. Four electronic searches (PubMed, Web of Science, Cochrane Library, and Science Direct) which were limited to articles on human studies on the effect of Twin Block (TB) and Forsus (FFRD) appliances in the treatment of Class II malocclusion between the years 2000 and 2020 were conducted. The data based on selected variables was analyzed using Comprehensive Meta Analysis (CMA) Version 3. Fifty-two studies were included, and fourteen studies were selected to be subjected to meta-analysis for Forsus, while a total of forty-eight studies were included and fourteen studies were selected to be included in the meta-analysis for Twin-block. When the p value (p<0.001) was taken into account for Twinblock, there was a significant decrease in the SNA, ANB and overjet value after the treatment. Also there was a significant increase in the SNB value after the treatment. When the p value (p<0.001) was taken into account for Forsus, there was a significant decrease in the SNA, ANB, overjet, overbite value after the treatment. Also, there was a significant increase in the SNB value after the treatment. Both FFRD and TB showed positive effects on the SNA, SNB, ANB and overjet values. However, while FFRD showed a positive effect on overbite TB did not exhibit a significant difference.

Bu sistematik literatür taraması ve meta-analizin birincil amacı, twin blok ve forsus apareyi ile ilgili seçilmiş yayınları, bu aygıtların genel iskeletsel ve dentoalveolar etkilerini saptamak için taramaktır. Bu çalışmanın ikincil amacı, her bir tedavi yaklaşımının ortak sonuçlarının bir karşılaştırmasını yapmaktadır. Sınıf II maloklüzyonu tedavisinde Twin Block (TB) ve Forsus (FFRD) apareylerinin etkisi üzerine yapılmış insan çalışmalarını içeren, 2000 ve 2020 yılları arasında yayınlanmış makalelerle sınırlı dört elektronik araştırmaya ilaveten (PubMed, Web of Science, Cochrane Library ve Science Direct), seçilmiş bu makalelerin referansları incelenerek bir dizi yeni makale bulunmuştur. Seçilen değişkenlere dayalı veriler Kapsamlı Meta Analiz (CMA) 3.sürüm kullanılarak analiz edilmiştir. Forsus için önce elli iki çalışma ayrılmış ve bunlardan on dört çalışma meta-analiz için seçilmiştir. Twin blok için toplam kırk sekiz çalışma ilk listeye dahil edilmiş ancak, meta-analiz için on dört çalışma seçilmiştir. Twinblock için p değeri (p<0,001) dikkate alındığında tedavi sonrası SNA, ANB ve overjet değerlerinde anlamlı bir düşüş olmuştur. Ayrıca tedaviden sonra SNB değerinde önemli bir artış gözlenmiştir. Ancak, overbite ile ilgili olarak twin block tedavisi sonrası bu ölçüm değerinde istatistiksel olarak anlamlı bir fark bulunmamıştır. Forsus için p değeri (p<0,001) dikkate alındığında, tedavi sonrası SNA, ANB, overjet, overbite değerlerinde anlamlı bir düşüş, ayrıca SNB değerinde önemli bir artış saptanmıştır. Hem forsus apareyi hem de twin block apareyi, SNA, SNB, ANB ve overjet değerleri üzerinde olumlu etkiler göstermiştir. Ancak FFRD overbite'ın üzerinde olumlu bir etki gösterirken, TB anlamlı bir fark yaratmamıştır. Bu sonuç, özellikle overbite'ın önemli olduğu Sınıf II maloklüzyonu tedavilerinde aparey seçimi yaparken dikkate alınmalıdır.
Gençler arasında sınıf II düzeltmede twin blok apareyi forsus apareyinin dış ve iskeletsel etkilerinin karşılaştırması için bir meta-analiz
Keywords: Class II Malocclusion; Dental Changes; Dentoalveolar Changes; Forsus Skeletal Changes; Skeletal Changes; Twin Block; Class II Malocclusion; Dental Changes; Dentoalveolar Changes; Forsus Skeletal Changes; Skeletal Changes; Twin Block